2020
DOI: 10.1038/s41598-020-71541-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention and representation of time intervals in childhood

Abstract: Spatial attention and spatial representation of time are strictly linked in the human brain. In young adults, a leftward shift of spatial attention by prismatic adaptation (PA), is associated with an underestimation whereas a rightward shift is associated with an overestimation of time both for visual and auditory stimuli. These results suggest a supra-modal representation of time left-to-right oriented that is modulated by a bilateral attentional shift. However, there is evidence of unilateral, instead of bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…On the other hand, since sensorimotor aftereffect and cognitive effect act at different levels, they are not consistently reported together, as suggested by other experiments exploring the effects of leftward PA in both healthy subjects and neurological patients. Schintu et al 19 reported modulation of left hemisphere dopaminergic activity in healthy subjects following leftward PA, without differences in the amount of sensorimotor effects induced by leftward vs. rightward PA. Frassinetti et al 13 first documented underestimation of time perception following leftward PA, a finding consistently replicated in other studies and correlated with the amount of sensorimotor effects 8 , 10 , 11 , 14 , 20 . In neurological patients, leftward PA has been shown to reshape visuospatial representation in left brain damaged patients with right neglect 67 69 .…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…On the other hand, since sensorimotor aftereffect and cognitive effect act at different levels, they are not consistently reported together, as suggested by other experiments exploring the effects of leftward PA in both healthy subjects and neurological patients. Schintu et al 19 reported modulation of left hemisphere dopaminergic activity in healthy subjects following leftward PA, without differences in the amount of sensorimotor effects induced by leftward vs. rightward PA. Frassinetti et al 13 first documented underestimation of time perception following leftward PA, a finding consistently replicated in other studies and correlated with the amount of sensorimotor effects 8 , 10 , 11 , 14 , 20 . In neurological patients, leftward PA has been shown to reshape visuospatial representation in left brain damaged patients with right neglect 67 69 .…”
Section: Discussionmentioning
confidence: 63%
“…In the exposure condition, 90 trials in visible pointing were administered; subjects wore prismatic lenses that induced a 20° shift of the visual field to the right or to the left. In the post-exposure condition, 30 trials in invisible pointing were administered immediately after removal of the prisms 20 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations